2002
DOI: 10.1002/mc.10027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differentially expressed genes in hepatocellular carcinoma using cDNA arrays

Abstract: Hepatocellular carcinoma (HCC) is characterized by multiple somatic mutations, including DNA rearrangements, that affect many cell-growth regulatory pathways. Many genes differentially expressed in HCC have been reported previously, but the patterns of expression varied significantly between patients who bore different risk factors for HCC. To identify genes whose differential expression could serve as a "signature" for diagnosis and prognosis of HCC, we performed analyses of differentially expressed genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 36 publications
(49 reference statements)
4
15
0
Order By: Relevance
“…Our reanalysis of five transcriptomic studies revealed an alteration of Rnd3 messenger RNA (mRNA) expression in HCC, compared to nontumor liver tissues,5 with four of five showing a down‐expression16‐19 and a single one, based on only four cases, an overexpression 20. Here, we confirm that Rnd3 is down‐regulated in most human HCC and HCC‐related cell lines, and we provide evidence that Rnd3 down‐regulation increases HCC invasion and thus may favor HCC progression.…”
supporting
confidence: 68%
“…Our reanalysis of five transcriptomic studies revealed an alteration of Rnd3 messenger RNA (mRNA) expression in HCC, compared to nontumor liver tissues,5 with four of five showing a down‐expression16‐19 and a single one, based on only four cases, an overexpression 20. Here, we confirm that Rnd3 is down‐regulated in most human HCC and HCC‐related cell lines, and we provide evidence that Rnd3 down‐regulation increases HCC invasion and thus may favor HCC progression.…”
supporting
confidence: 68%
“…Among the HCC-related microarray studies, EHCO was further reorganized into five gene sets. Differentially expressed HCC-related gene sets were collected from four major studies, including Chen et al, [1] (referred to as SMD1648), Neo et al, [2] (referred to as GIS), Lee et al, [3] (referred to as Lee_NIH), and Kim et al, [4] (referred to as Kim_NIH), and ten additional reports [5-14], which were manually keyed in and are referred to as TableX_mRNA. The differentially expressed genes collected from these sets ranged from 199 (GIS) to 1,161 (SMD1648).…”
Section: Resultsmentioning
confidence: 99%
“…These include schwannoma [28], glioma [29], hepatocellular carcinoma [30], melanoma [27,31], transitional cell carcinoma [32], prostatic adenocarcinoma [33,34] and meningioma [35]. ON has been shown to directly affect tumor invasion in in vivo models, including ON-null mice [27,34,36] and has been correlated with tumor prognosis in melanomas and transitional cell carcinoma of the bladder [31,32].…”
Section: Discussionmentioning
confidence: 99%